1998
DOI: 10.1016/s0741-5214(98)70207-1
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic aneurysm rupture rates: A 7-year follow-up of the entire abdominal aortic aneurysm population detected by screening

Abstract: In centers with an operative mortality rate of greater than 2%, (1) surgical intervention is not indicated for asymptomatic AAAs of less than 4.5 cm in diameter, and (2) elective surgery should be considered only for patients with aneurysms between 4.5 and 6 cm in diameter that are expanding by more than 1 cm per year or for patients in whom symptoms develop. In centers with elective mortality rates of greater than 10% for abdominal aortic aneurysm (AAA) repair, the benefit to the patient of any surgical inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(44 citation statements)
references
References 27 publications
0
40
0
4
Order By: Relevance
“…23 An exception to this guideline is that intervention should be offered despite the size of the aneurysm if symptoms develop or the aneurysm increases in size by 1 cm per year. 24 In addition, if the patient is a woman with smaller native vessels, the relative size that represents aneurysmal disease may be less than the conventional 5 to 5.5 cm range.…”
Section: Indications For Aaa Treatmentmentioning
confidence: 99%
“…23 An exception to this guideline is that intervention should be offered despite the size of the aneurysm if symptoms develop or the aneurysm increases in size by 1 cm per year. 24 In addition, if the patient is a woman with smaller native vessels, the relative size that represents aneurysmal disease may be less than the conventional 5 to 5.5 cm range.…”
Section: Indications For Aaa Treatmentmentioning
confidence: 99%
“…[11][12][13] There is no proven effective treatment for these small aneurysms, and repeated scans are used to monitor the expansion of the aneurysm until the diameter of the aneurysm is Ͼ5.5 cm. At this stage, the risk of rupture is greater than the risk of operation, and surgery is indicated.…”
Section: See P 405mentioning
confidence: 99%
“…As a result, is the main factor in the decision to recommend repair or just submit the patient to periodic clinical surveillance. [20][21][22] Several randomized trials have identified the 5cm size limit for the indication of surgical approach open23. However, if there was any procedure with morbidity and survival uniforms, all aneurysms would be treated, regardless of their size.…”
Section: Treatmentmentioning
confidence: 99%